Credit ratings and cross-border bond market spillovers - Benjamin Böninghausen; Michael Zabel (European Central Bank (ECB), 2015)
This paper studies spillovers across sovereign debt markets in the wake of sovereign rating changes. We compile an extensive dataset covering all announcements by the three major agencies (Standard & Poor's, Moody's, Fitch) and daily sovereign bond market movements of up to 73 developed and emerging countries between 1994 and 2011. To cleanly identify the existence of spillover effects, we perform an explicit counterfactual analysis which pits bond market reactions to small revisions in ratings against reactions to all other, more major changes. We also control for the environment in which an announcement is made, such as the anticipation through watchlistings and the interaction of similar rating actions by different agencies. While there is strong evidence of negative spillover effects in response to downgrades, positive spillovers from upgrades are much more limited at best. Furthermore, negative spillover effects are more pronounced for countries within the same region. Strikingly, this cannot be explained by fundamental linkages and similarities between countries.
Keywords: G15; F36; 330; credit rating agencies; cross-border spillover effects; international financial integration; Sovereign debt market